Coherence: a new approach for analyzing interrelated serial data - Rebekka Mumm; Detlef Groth; Michael Hermanussen (Human Biology and Public Health)
Background Serial public health data may or may not reflect living conditions, political background and/or certain targeted health interventions. Yet, the effect of political events and/or health interventions that only last for a few years or a single legislative period may be difficult to analyze as restricting the range of the variables, i.e. the time interval within which the data were obtained, restricts the power of correlation analyzes.